Is It Too Much English? - FIRICĂ, Camelia (Journal of Research in Educational Sciences, 2016)
The linguistic contact incurred influences which languages manifested on each other, whether stronger - a language’s strength comes from the cultural, political, military power of the people who speak it - or weaker. Linguistic influences have been met differently by the natives of the recipient languages but, irrespective of standpoints, the phenomenon is irreversible. It is so much noticeable nowadays when people witness linguistic globalization through the extensive use of English which, in its turn, borrowed thousands of words from the languages with which it has been in contact. After the fall of the communism due to the opening to the West that the new historical conditions imposed by their political, social and cultural aspects, Romanian language underwent, from the point of view of its vocabulary, changes meant to express the surrounding realities. The paper aims to highlight, based on opinions expressed in a survey, the attitudes and linguistic behaviour of the teaching members of the Faculty of Juridical, Economic and Administrative Sciences, Spiru Haret University towards the overuse of English loanwords in everyday life.
Keywords: Anglicism; loanword; language; use; English; Romanian.